The Analysis Of Business Ethics In The Management Of Private College - Kamaludin, Kamaludin (Journal of World Science, 2022)
This research aims to determine and examine how the application of business ethics in the management of private college. This research belongs to a qualitative study based on the type of data and the analysis. Research focus is business ethics, the source of the data is primary data and secondary data. The techniques of collecting data is using interviews, library research and observation. Meanwhile the instrument of the research is the researcher himself. The result of this research is hypothesized that private universities have not applied business ethics in their management, it can be found through the high study cost to the students because they are regarded as the commodity. Private college that should make the balance of the business mission, social mission, and religious mission. There is a new perspective through the opened management of using funds, students or the community will conclude that the study cost of private university is not high or expensive but measurable